Decolourization of Textile Azo Dyes by using Bacteria Isolated from Textile Dye Effluent - P. Ganesh, M. Manivannan*, D. Reetha and (Journal of Ecobiotechnology, 2011)
The present study was carried out to isolate dye decolourizing bacteria and to study the dye decolourizing ability.Ã‚Â Different bacterial isolate such as, Bacillus sp., Escherichia coli and Pseudomonas fluorescens were isolated from textile dye effluent sample and used for the decolourization study. It was noticed that there was a decrease in the OD in all the three species of all the five dyes as the incubation period increased. Pseudomonas fluorescens was more effective followed by Bacillus, and Escherichia coli. It was found that all the isolated bacteria were efficient decolourizers of Orange 3R.Ã‚Â The decolourization of dye amounted to 59, 77, 79 respectively within 16 days.Ã‚Â Yellow GR was recalcitrant to decolourization, the O.D. value from an initial value of 0.6912 was reduced only to 0.303 and from 0.746 to 0.218, 1.236, to 1.33 by Pseudomonas fluorescens, Bacillus sp. and Escherichia coli respectively. Percentage decolourization was 43%, 15%, 90% respectively. The percentage of decolourization of Orange GR is slightly higher than Blue 3R and the percentage decolourization of Black RL is similar to T Blue.